Upaya Pimpinan Pondok Pesantren dalam Meningkatkan Pemahaman Materi Al Miftah Lil Ulum Melalui Microsoft Powerpoint di Pondok Pesantren Syaichona Cholil Kutai Timur Tahun Pelajaran 2023/2024 - Effendi, Suhlal; Minarsih, Minarsih (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
This study employs a qualitative approach to explore the efforts of Syaichona Cholil Islamic Boarding School leaders in enhancing students' understanding of the Al Miftah Lil Ulum method through Microsoft PowerPoint during the 2023/2024 academic year. The research reveals that utilizing Microsoft PowerPoint as a learning medium has significantly benefited students. The study aims to deepen students' comprehension of Al Miftah Lil Ulum using Microsoft PowerPoint, demonstrating improvements in students' abilities to explain, recall, and apply learning materials. Additionally, students have shown increased confidence in conveying acquired knowledge and in learning practices, particularly in reading traditional Islamic texts. In conclusion, the use of Microsoft PowerPoint in teaching Al Miftah Lil Ulum at Syaichona Cholil Islamic Boarding School in East Kutai has evidenced enhanced student understanding, indicating digital technology's effective role in supporting learning within traditional Islamic educational settings and its potential positive impact on future religious education quality.